The revised Patient Perception of Patient‐Centeredness Questionnaire: Exploring the factor structure in French‐speaking patients with multimorbidity - Tu Ngoc Nguyen; Patrice Alain Ngangue; Bridget L. Ryan; Moira Stewart; Judith Belle Brown; Tarek Bouhali; Martin Fortin (Wiley, 2020)
Abstract Background The Patient Perception of Patient‐Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC‐R) in French‐speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient‐Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health‐care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC‐R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC‐R showed very good internal consistency, with three factors: Patient‐Centered Clinical Method (PCCM) Component 1‐Exploring the health, disease and illness experience + PCCM Component 4‐Enhancing the patient-clinician relationship (Factor 1); PCCM Component 2‐Understanding the whole person (Factor 2); and PCCM Component 3‐Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC‐R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient‐centeredness.